Spherical aluminum oxide as well as preparation method and application thereof
By pre-drying, aging and water vapor treatment during the preparation of spherical alumina, the problem of insufficient strength and spherical degree of spherical alumina is solved, the performance and production efficiency of spherical alumina are improved, and the cost and pollution are reduced.
Patent Information
- Application Number
- CN202310781792.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-03
AI Technical Summary
In the existing spherical alumina preparation method, it is difficult to simultaneously improve the spherical shape and strength, resulting in easy damage to the carrier in application, high wear rate, and polluted gases are generated during roasting, which increases production costs.
Spherical alumina was prepared by dropping the aluminum hydroxide slurry into a ball column to make wet pellets, pre-drying and aging, then water vapor treatment at a specific temperature, and finally drying and calcining.
It significantly improves the spherical shape and strength of spherical alumina, reduces production costs, reduces the production of polluted gases, and extends the service life of the catalyst.
Smart Images

Figure BDA0004311006430000171 
Figure BDA0004311006430000181
Abstract
Description
Technical Field
[0001] The invention relates to the field of spherical alumina preparation, and in particular to spherical alumina and a preparation method and application thereof. Background Art
[0002] Alumina has become one of the most widely used industrial catalyst carriers due to its suitable pore distribution, surface acidity, good thermal stability and large specific surface area. In different application fields, due to different process conditions, the requirements for the size and shape of alumina carriers are different. For example, in fixed bed processes such as catalyst hydrogenation, strip-shaped and clover-shaped alumina are generally used as catalyst carriers, while in moving bed continuous reforming and low-carbon alkane dehydrogenation processes, spherical alumina is required as a catalyst carrier.
[0003] In moving bed processes such as continuous reforming and dehydrogenation of low-carbon alkanes, the physicochemical properties of the spherical alumina carrier used in the catalyst are relatively stringent. Since the catalyst is continuously transported and regenerated in the device, in order to reduce the mechanical wear of the catalyst during the production process, the sphericity and strength of the spherical alumina carrier are required to be high; in order to allow the catalytic active metal to be evenly distributed on the alumina carrier, it is required to have a large specific surface area and a suitable pore structure; in addition, another important physical property of the spherical alumina carrier is the bulk density. In the continuous reforming device, the appropriate bulk density allows a lower catalyst loading to be obtained while achieving the catalytic reaction effect and process requirements, thereby reducing the total amount of catalyst and the amount of platinum used in platinum-containing precious metal catalysts, and reducing production costs. The bulk density of the currently commonly used continuous reforming catalysts is between 0.5 and 0.8 g / mL, and is mainly divided into two series, conventional bulk density catalysts and high bulk density catalysts. Conventional bulk density is about 0.5-0.6 g / mL, and high bulk density is 0.6-0.7 g / mL. Higher bulk density can overcome the wall adhesion effect caused by increased processing capacity of the device and increase the allowable processing capacity range of the device, but it will also increase the loading amount of the catalyst and increase the capital investment of the catalyst. In order to obtain reforming catalysts with different bulk densities, it is necessary to adjust the corresponding preparation conditions during the carrier preparation process to obtain spherical alumina carriers with different bulk densities.
[0004] Since the 1990s, people have conducted a lot of research on the forming methods of spherical alumina. At present, the more mature methods include rotation ball forming method, spray ball forming method, hot oil column ball forming method and oil ammonia column ball forming method. At present, the spherical alumina carriers used in continuous reforming, low-carbon alkane dehydrogenation catalysts, etc. are all prepared by oil ammonia column or hot oil column forming. In the oil ammonia column forming, pseudo-boehmite powder is generally used as the raw material, and an appropriate amount of acid is added and fully stirred to obtain a pseudo-boehmite dispersion, which is then dripped into the oil ammonia column for forming. The upper layer of the oil ammonia column is the oil layer, and the lower layer is the ammonia water layer. The main function of the oil layer is to make the dripped pseudo-boehmite slurry form a regular sphere under the action of surface tension, and the function of the ammonia water layer is to solidify the aluminum hydroxide balls formed in the oil layer, and then the aluminum hydroxide balls are dried and calcined to obtain spherical alumina carriers.
[0005] In the current industrial production of preparing spherical alumina carriers by oil-ammonia column molding, in order to adjust the packing density of the spherical alumina carrier, it is generally necessary to add pore-enlarging agents such as kerosene, liquid paraffin, activated carbon, cellulose, starch, etc. to the aluminum hydroxide slurry to form pores, thereby reducing the packing density of the spherical alumina carrier and obtaining a larger pore size. The packing density of the prepared spherical alumina carrier can be adjusted by adjusting the amount of the pore-forming agent added. In order to make the pore-forming agent evenly distributed, it is also necessary to add surfactants, emulsifiers, etc. to the aluminum hydroxide slurry.
[0006] US4542113 discloses a method for preparing spherical alumina by oil-ammonia column molding, wherein 20-30% of boehmite powder and 70-80% of pseudo-boehmite powder are used as raw materials, and an appropriate amount of acid is added to disperse and prepare an aluminum hydroxide slurry with a solid content of 20-40% by mass. In order to maintain the stability of the viscosity of the aluminum hydroxide slurry, 3-5% of urea is added thereto as a viscosity stabilizer. In order to adjust the packing density of the spherical alumina, a certain amount of kerosene is added as a pore expander, and an appropriate amount of surfactant is added to make the kerosene evenly distributed. Then the mixed slurry is dripped into the oil-ammonia column to form it, thereby preparing a spherical alumina carrier.
[0007] CN101850997A discloses an oil-ammonia column molding method for spherical alumina. Pseudo-boehmite powder is used as a raw material, water is added to form a slurry, urea is added to the slurry, and then acid is added to acidify the pseudo-boehmite to form a sol. In order to adjust the bulk density of the spherical alumina, kerosene is added as a pore-expanding agent, and an emulsifier with a hydrophilic-lipophilic balance value greater than 10 is added to evenly disperse the kerosene, stirred to form an emulsified slurry, and then molded in an oil-ammonia column, and the wet balls are collected, dried, and roasted to obtain spherical alumina.
[0008] CN103011213A discloses a method for preparing spherical alumina by using oil-ammonia column molding, wherein pseudo-boehmite acidified slurry and non-ionic surfactant solution are simultaneously dripped into the oil-ammonia column for molding, and the non-ionic surfactant solution uses a mixture of water and alcohol as a solvent. In order to adjust the packing density of the spherical alumina carrier, kerosene and an appropriate amount of emulsifier are added to the pseudo-boehmite slurry as a pore-enlarging agent.
[0009] CN106348326A discloses a gamma alumina and its preparation method, application and equipment. The method uses boehmite or aluminum hydroxide as an aluminum source, mixes 40 to 80 parts by weight of an aluminum source material, 3 to 20 parts by weight of an inorganic pore expander, and 1 to 20 parts by weight of an organic pore expander by a conventional method, and in the alumina preparation equipment described therein, the mixed powder is added to a combustion furnace and roasted at a high temperature to generate macroporous alumina, or it can be slurried into a liquid mixture and then dried. The aluminum source material is selected from boehmite, the inorganic pore expander is selected from ammonium bicarbonate, and the organic pore expander is selected from PEG200.
[0010] CN104891539A discloses a pore expansion method for spherical alumina particles. Pseudo-boehmite is dispersed in water to obtain a pseudo-boehmite suspension, and in order to adjust the bulk density of the spherical alumina carrier, liquid paraffin and activated carbon are added to the pseudo-boehmite suspension as pore expanders, and a surfactant is added at the same time, and an emulsified suspension is formed after homogenization and emulsification, and then an auxiliary agent selected from zinc powder, aluminum powder, zinc oxide powder or basic zinc carbonate is added, and then an aqueous solution of soluble alginate with a mass concentration of 1.5-4.0% is added to the above emulsified suspension to prepare a mixed slurry, and then the mixed slurry is dripped into an aqueous solution of aluminum, calcium, barium, copper, zinc, manganese or cobalt metal cations to form, and then dried and roasted to obtain a spherical alumina product.
[0011] In the spherical alumina preparation methods disclosed in the above patent applications, kerosene, liquid paraffin, activated carbon and other pore enlarging agents are added to the boehmite or pseudo-boehmite slurry to adjust the packing density and pore structure of the spherical alumina carrier. The added pore enlarging agents are difficult to recover and can only be removed by roasting, which not only produces a large amount of polluting gases to pollute the environment, but also increases the preparation cost of the spherical alumina carrier.
[0012] CN113735614A discloses a method for preparing spherical alumina, wherein an alumina sol made of pseudo-boehmite is dripped into an oil-ammonia column to form wet gel balls, and then the wet gel balls are taken out and placed in a C5-C10 fatty alcohol or a C5-C20 alkane for aging, and finally dried and roasted to obtain a spherical alumina carrier. The process can adjust the bulk density of the spherical alumina by changing the aging conditions of the aluminum hydroxide gel balls, does not need to add a pore-enlarging agent to the aluminum hydroxide slurry, and does not generate a large amount of polluting gas during the roasting process, thereby greatly reducing the production cost of the spherical alumina.
[0013] However, in the production process of spherical alumina carriers using the above process, the aging treatment of wet aluminum hydroxide gel beads in organic solvents often leads to a decrease in the strength and sphericity of the spherical alumina carriers. Therefore, how to regulate the packing density of the spherical alumina carrier while maintaining its high strength and good sphericity requires further research. Summary of the invention
[0014] The purpose of the present invention is to overcome the problem that the strength and sphericity of spherical alumina in the prior art need to be further improved, and to provide a spherical alumina and a preparation method and application thereof. The spherical alumina prepared by the preparation method provided by the present invention has the advantages of high sphericity and high strength.
[0015] In order to achieve the above object, the present invention provides a method for preparing spherical alumina, which comprises the following steps:
[0016] (1) dropping aluminum hydroxide slurry into a spheroidizing column to form wet aluminum hydroxide spheres, and then pre-drying the wet aluminum hydroxide spheres;
[0017] (2) aging the pre-dried product in the presence of a solvent;
[0018] (3) The product obtained by aging in step (2) is subjected to steam treatment at 100-240° C., and then optionally dried and calcined.
[0019] Preferably, the pre-drying in step (1) includes a first pre-drying and a second pre-drying.
[0020] Preferably, the first pre-drying conditions include: a temperature of 30-60° C., preferably 30-50° C.; and a time of 20-180 minutes, preferably 30-120 minutes.
[0021] Preferably, the heating rate of the first pre-drying is 1-5°C / min, preferably 1-3°C / min.
[0022] Preferably, the second pre-drying conditions include: a temperature of 70-120° C., preferably 90-120° C.; and a time of 30-420 minutes, preferably 30-180 minutes.
[0023] Preferably, the heating rate of the second pre-drying is 5-10°C / min, preferably 5-8°C / min.
[0024] Preferably, the time for the water vapor treatment in step (3) is 10-60 minutes, preferably 10-30 minutes.
[0025] Preferably, the volume space velocity of water vapor in step (3) is 100-1000h -1 ; preferably 200-600h -1 .
[0026] The inventors of the present invention adopt the oil-ammonia column spheroidization method to prepare spherical alumina in CN113735614A. The process method adjusts the bulk density of spherical alumina by changing the aging conditions of aluminum hydroxide gel balls, does not require the addition of pore-enlarging agents to the aluminum hydroxide slurry, and does not generate a large amount of polluting gas during the roasting process, thereby greatly reducing the production cost of spherical alumina. However, in this method, both the sphericity and particle strength are reduced. Therefore, how to further improve the sphericity and particle strength at the same time becomes the key to the research.
[0027] In the preparation method provided by the present invention, the obtained wet aluminum hydroxide pellets are pre-dried and then aged, and then the aged product is treated with water vapor at a specific temperature, so that the sphericity and particle strength of the obtained spherical aluminum oxide can be significantly improved.
[0028] The second aspect of the present invention provides spherical alumina prepared by the method described in the first aspect.
[0029] The third aspect of the present invention provides a use of the spherical alumina described in the second aspect in a catalyst.
[0030] Through the above technical solution, the beneficial effects of the present invention include:
[0031] The spherical aluminum oxide prepared by the preparation method provided by the invention has the advantages of high sphericity and high strength. DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] One aspect of the present invention provides a method for preparing spherical alumina, the method comprising the following steps:
[0034] (1) dropping aluminum hydroxide slurry into a spheroidizing column to form wet aluminum hydroxide spheres, and then pre-drying the wet aluminum hydroxide spheres;
[0035] (2) aging the pre-dried product in the presence of a solvent;
[0036] (3) The product obtained by aging in step (2) is subjected to steam treatment at 100-240° C., and then optionally dried and calcined to obtain spherical alumina.
[0037] The inventors of the present invention have found that pre-drying wet aluminum hydroxide pellets before aging can significantly improve the sphericity and strength of aluminum oxide.
[0038] According to the present invention, preferably, the pre-drying in step (1) includes a first pre-drying and a second pre-drying.
[0039] According to the present invention, preferably, the first pre-drying conditions include: a temperature of 30-60° C., preferably 30-50° C.; and a time of 20-180 minutes, preferably 30-120 minutes.
[0040] According to the present invention, preferably, the heating rate of the first pre-drying is 1-5°C / min, preferably 1-3°C / min.
[0041] According to the present invention, preferably, the second pre-drying conditions include: a temperature of 70-120° C., preferably 90-120° C.; and a time of 30-420 minutes, preferably 30-180 minutes.
[0042] According to the present invention, preferably, the heating rate of the second pre-drying is 5-10° C. / min, preferably 5-8° C. / min.
[0043] According to the present invention, preferably, the solid content of the aluminum hydroxide slurry is 6-25wt%, preferably 15-25wt%.
[0044] The aluminum hydroxide slurry of the present invention does not add other solvents such as pore expanders, and does not generate pollutant gases generated by the use of pore expanders during the subsequent roasting process, while also reducing the production cost of spherical alumina. Preferably, the aluminum hydroxide slurry is obtained by mixing an aluminum-containing precursor, an acid and water.
[0045] According to a specific embodiment of the present invention, pseudo-boehmite powder is first mixed with acid, and then water is added for second mixing to obtain aluminum hydroxide slurry.
[0046] The present invention has a wide range of choices for the types of aluminum-containing precursors, which can be conventionally selected in the art.
[0047] Preferably, the aluminum-containing precursor is pseudo-boehmite and / or boehmite, preferably pseudo-boehmite.
[0048] In the present invention, the aluminum-containing precursor may be in the form of dry powder, or may be an aluminum hydroxide filter cake or slurry prepared from its synthetic raw materials. The present invention preferably uses a dry powder aluminum-containing precursor.
[0049] The present invention has a wide range of choices for the type of acid, which can be selected according to conventional methods in the art. Preferably, the acid is an inorganic acid and / or an organic acid.
[0050] Preferably, the inorganic acid is nitric acid and / or hydrochloric acid, and the organic acid is formic acid and / or acetic acid.
[0051] In order to optimize the effect of oil-ammonia column sphering, preferably, the mass ratio of the acid to the aluminum-containing precursor is 0.01-0.06, wherein the aluminum-containing precursor is calculated as aluminum oxide.
[0052] According to the present invention, preferably, the acid is provided in the form of an acid solution, and the concentration of the acid solution is 0.5-6% by mass.
[0053] The present invention has no particular limitation on the amount of water used, provided that the solid content of the aluminum hydroxide slurry is in the range of 6-25wt%.
[0054] According to the present invention, preferably, the spheroidizing column comprises an organic phase and an ammonia aqueous phase, and the ratio of the thickness of the organic phase to the thickness of the ammonia aqueous phase is 1:10-80, preferably 1:20-60.
[0055] Preferably, the thickness of the aqueous ammonia phase is 100-300 cm.
[0056] According to the present invention, preferably, the organic phase is C5-C 20 The alkane is preferably at least one selected from gasoline, kerosene, petroleum ether, n-pentane, n-hexane, n-heptane, n-octane and undecane.
[0057] According to the present invention, preferably, the concentration of the ammonia water is 5-15% by mass.
[0058] The present invention has no particular limitation on the process of preparing wet aluminum hydroxide pellets, and the process can be carried out in accordance with conventional methods in the art. Preferably, the step (1) of dripping aluminum hydroxide slurry into a pelletizing column to prepare wet aluminum hydroxide pellets comprises: dripping aluminum hydroxide slurry into an organic phase of a pelletizing column to form pellets, and then entering an ammonia aqueous phase to solidify for 0.2-12 hours, preferably 0.5-6 hours, to form wet aluminum hydroxide pellets.
[0059] Specifically, the step (1) of dripping aluminum hydroxide slurry into a ball-forming column to form wet aluminum hydroxide balls comprises: dripping aluminum hydroxide slurry into an oil-ammonia column through a ball-dropping device with a needle, and due to the effect of surface tension, the droplets shrink into a spherical shape when passing through the upper organic phase layer, and then enter the ammonia water layer to solidify for 0.2-12 hours to form wet aluminum hydroxide balls, which are collected at the bottom of the oil-ammonia column.
[0060] The preparation method of the present invention can flexibly adjust the bulk density within the range of 0.3-0.75 g / ml by adjusting the aging conditions. Preferably, the aging conditions in step (2) include: a temperature of 60-300° C., preferably 60-220° C.; and a time of 5-30 hours, preferably 5-20 hours.
[0061] The present invention has no particular limitation on the amount of the solvent used, and the amount can be prepared by referring to conventional methods in the art, and the present invention does not impose any limitation thereto.
[0062] According to the present invention, preferably, the solvent is selected from C4-C 10 Fatty alcohols and / or C5-C 20 of alkanes.
[0063] When the solvent is C4-C 10 When the fatty alcohol is C4-C 10 The fatty alcohol is selected from at least one of n-butanol, n-pentanol, n-hexanol, n-heptanol and n-octanol.
[0064] Preferably, the C4-C 10 The fatty alcohols are normal primary alcohols.
[0065] When the solvent is C5-C 20 When the alkane is C5-C 20 The alkane is selected from at least one of pentane, hexane, heptane, octane, nonane, decane and petroleum ether.
[0066] Preferably, the C5-C 20 The alkanes are normal alkanes.
[0067] Preferably, the method further comprises: firstly subjecting the product obtained by aging in step (2) to solid-liquid separation to obtain a solid product, and then subjecting the solid product to steam treatment.
[0068] The present invention has no particular limitation on the solid-liquid separation method, and the solid-liquid separation can be carried out by referring to conventional technical means in the art.
[0069] The inventors of the present invention have found that subjecting the aged product to a specific water vapor treatment can significantly improve the sphericity and strength of alumina.
[0070] The water vapor treatment of the present invention is beneficial to improving the strength and sphericity of spherical alumina. Preferably, the temperature of the water vapor treatment in step (3) is 100-180°C, for example, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, and any value in the range formed by any two of these values. The use of this preferred embodiment is beneficial to improving the strength and sphericity of spherical alumina. When the temperature of the water vapor treatment exceeds this range, the excessively high steam temperature will cause cracks in the alumina balls, thereby reducing their strength; when the temperature of the water vapor treatment is lower than this range, the water vapor treatment time is too long, which will cause a reduction in sphericity.
[0071] Preferably, the steam treatment time in step (3) is 10-60 minutes, preferably 10-30 minutes, for example, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, and any value in the range formed by any two of these values. By adopting this preferred embodiment, the strength and sphericity of the spherical alumina can be further improved.
[0072] According to the present invention, preferably, the volume space velocity of the water vapor is 100-1000h -1 , preferably 200-600h -1 , for example, it can be 100h -1 , 150h -1 , 200h -1 , 250h -1 、300h -1 、350h -1 , 400h -1 , 450h -1 , 500h -1 、550h -1 、600h -1 、650h -1、700h -1 、750h -1 , 800h -1 、850h -1 , 900h -1 、950h -1 、1000h -1 , and any value in the range formed by any two of these values. By adopting this preferred embodiment, the strength and sphericity of the spherical alumina can be further improved.
[0073] In the present invention, unless otherwise specified, the term "optionally" means containing or not containing, adding or not adding, adopting or not adopting. Specifically, step (3) of the present invention may be dried or not dried.
[0074] The present invention has no particular limitation on the drying, and the drying can be carried out according to the commonly used methods in the art. Preferably, the drying conditions in step (3) include: a temperature of 50-150° C. and a time of 5-24 hours.
[0075] Preferably, the drying conditions include: first drying at 50-80° C. for 6-12 hours, and then drying at 90-150° C. for 2-8 hours.
[0076] The present invention has no particular limitation on the calcination, and the calcination can be carried out according to the commonly used methods in the art. Preferably, the calcination temperature in step (3) is 450-750° C., and the time is 2-10 hours. The calcination is generally carried out in an air atmosphere, which can include a flowing atmosphere or a static atmosphere.
[0077] According to a particularly preferred embodiment of the present invention, a method for preparing spherical alumina comprises the following steps:
[0078] (1) dropping aluminum hydroxide slurry into a spherical column to prepare wet aluminum hydroxide spheres, and then pre-drying the wet aluminum hydroxide spheres to obtain a solid product;
[0079] (2) aging the solid product in the presence of a solvent;
[0080] (3) treating the product obtained by aging in step (2) with steam at 100-180° C., and then optionally drying and calcining to obtain spherical alumina;
[0081] The volume space velocity of the water vapor is 200-600h -1 ;
[0082] The steam treatment time is 10-30 minutes;
[0083] The pre-drying in step (1) includes a first pre-drying and a second pre-drying;
[0084] The first pre-drying conditions include: temperature of 30-50°C; time of 30-120 minutes;
[0085] The heating rate of the first pre-drying is 1-3°C / min;
[0086] The second pre-drying conditions include: temperature of 90-120°C; time of 30-180 minutes;
[0087] The heating rate of the second pre-drying is 5-8°C / min.
[0088] By adopting the preparation method provided by the present invention, the sphericity and strength of the prepared spherical aluminum oxide can be further significantly improved.
[0089] In the present invention, the "first" and "second" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.
[0090] The second aspect of the present invention provides spherical alumina prepared by the method described in the first aspect.
[0091] The spherical alumina of the present invention has the advantages of high sphericity and high strength.
[0092] According to the present invention, preferably, the sphericity of the spherical alumina is greater than 0.99.
[0093] The sphericity of the spherical alumina described in the present invention is measured by using a CAMSIZER multifunctional particle size analyzer produced by RETSCH of Germany.
[0094] According to the present invention, preferably, the Q of the spherical alumina 0.95 Greater than 98% by volume, wherein Q 0.95 It is the volume proportion of spherical alumina particles with a sphericity greater than 0.95 in all spherical alumina particles.
[0095] According to the present invention, preferably, the crushing strength of the spherical alumina is 80-130N / grain.
[0096] The crushing strength of the spherical alumina of the present invention is measured by using a DL4 particle strength tester.
[0097] The third aspect of the present invention provides a use of the spherical alumina described in the second aspect in a catalyst.
[0098] The spherical alumina prepared by the method of the present invention is suitable as a catalyst carrier, preferably suitable as a carrier of continuous reforming catalysts, light alkane dehydrogenation catalysts and other catalysts, and more suitable as a carrier of continuous reforming catalysts loaded with precious metals, light alkane dehydrogenation catalysts and other catalysts.
[0099] The present invention will be described in detail below through examples.
[0100] In the following examples, the method for determining the property parameters of the alumina spheres is as follows:
[0101] (1) The specific surface area and pore volume were measured using the Autosorb-6B fully automatic specific surface area and porosity analyzer from Quantachrome, USA.
[0102] Determination method: Before the test, the alumina ball sample was vacuum degassed at 1.33Pa and 300℃ for 4h, and then isothermally adsorbed and desorbed at liquid nitrogen temperature of 77.4K (-196℃) with high-purity nitrogen as the adsorption medium, and the isotherm was determined; the specific surface area was calculated using the BET (Brunauer-Emmett-Teller) equation, and the pore volume and pore size distribution were calculated from the desorption isotherm using the BJH equivalent cylinder model.
[0103] (2) The crushing strength of alumina pellets was measured using a DL4 particle strength tester (produced by Dalian Penghui Technology Development Co., Ltd.).
[0104] The determination method is as follows: dry the alumina pellets at 120°C for 2 hours, cool them in a dryer to 25°C, and take out 50 pellet samples to be tested. Set the relevant measurement parameters of the particle strength tester, place a pellet sample to be tested on the sample table, click the measurement button, and the force rod slowly drops to increase the pressure until the pellet sample is broken, and record the pressure data. Remove the maximum and minimum values of the pressure data of the 50 pellets, and take the average value of the other data, which is the crushing strength of the test pellet sample.
[0105] (3) The method for determining the bulk density of the alumina spheres in the embodiment is as follows: add the alumina spheres to a 100 mL graduated cylinder. During the addition process, tap the cylinder with appropriate force to make the alumina spheres compactly stacked until the volume of the spheres in the cylinder is 100 mL and the volume does not change with tapping. Assuming the total mass of the cylinder and the alumina spheres is M1, in grams, and the mass of the cylinder is M2, in grams, then the bulk density of the alumina spheres is ρ 堆积 =(M1-M2) / 100, unit: g / mL.
[0106] (4) The sphericity of alumina spheres was measured using a CAMSIZER multifunctional particle size analyzer from RETSCH, Germany.
[0107] Determination method: Take 50mL of alumina pellets; put the sample in an oven, heat it from room temperature to 150℃±5℃ in 30 minutes, keep it at a constant temperature for 2 hours, take it out, put it in a desiccator and cool it to room temperature for testing.
[0108] After setting the relevant measurement parameters of the particle size and shape analyzer, put the alumina balls into the feed hopper of the particle size and shape analyzer. The vibrating feeder controls the transmission and dispersion of the alumina balls through vibration and makes them fall into the image acquisition and measurement area through free fall. The alumina balls are illuminated by light during the falling process, and the high-speed camera of the image acquisition device takes pictures at the same time. The instrument uses the built-in algorithm to analyze and derive the particle size and sphericity of the alumina balls. The alumina balls that fall are collected in the collection box.
[0109] The proportion (volume) of particles with a sphericity (SPHT) greater than 0.95 in the total particles of the alumina pellet sample is expressed by Q 0.95 express.
[0110] Example 1
[0111] (1) Preparation of aluminum hydroxide slurry
[0112] Take 100g of pseudo-boehmite powder (alumina content of 72.5% by mass), add 62.5g of 4.6% by mass nitric acid for dispersion, and then add 200g of deionized water to obtain aluminum hydroxide slurry with a solid content of 20% by mass.
[0113] (2) Preparation of aluminum hydroxide pellets
[0114] The aluminum hydroxide slurry prepared in step (1) is dripped into the oil-ammonia column. The upper layer of the oil-ammonia column is the oil phase, and the lower layer is the ammonia water phase. The upper oil phase is 3 cm thick n-octane, and the lower ammonia water phase is 150 cm thick ammonia water with a concentration of 8% by mass. The aluminum hydroxide slurry is dripped into the oil phase in the oil-ammonia column to form small balls, and then enters the ammonia water phase and stays in the ammonia water phase for 0.5 hours to solidify, forming wet aluminum hydroxide small balls, which are collected at the bottom of the oil-ammonia column. The wet aluminum hydroxide small balls are taken out and pre-dried: first, the temperature is increased to 45°C at a heating rate of 3°C / min, and dried for 60 minutes, and then the temperature is increased to 90°C at a heating rate of 5°C / min, and dried for 120 minutes.
[0115] (3) Preparation of alumina balls
[0116] The pre-dried aluminum hydroxide balls are collected for aging. The specific steps are as follows: the pre-dried aluminum hydroxide balls are placed in 300 mL of n-pentanol and aged at 120°C for 6 hours. After aging, the n-pentanol is filtered out to obtain aged aluminum hydroxide balls. The aged aluminum hydroxide balls are treated at 120°C for 15 minutes under the action of water vapor, and the space velocity of the water vapor is 500h-1 The aluminum hydroxide balls treated with water vapor were dried at 80°C for 8 hours, 120°C for 4 hours, and then calcined at 600°C for 3 hours to obtain γ-Al2O3 small ball particles with smooth outer surface. The sphericity, crushing strength, bulk density and pore volume of the γ-Al2O3 small balls were measured, and the results are shown in Table 1.
[0117] Example 2
[0118] (1) Preparation of aluminum hydroxide slurry
[0119] Take 100g of pseudo-boehmite powder (alumina content of 72.5% by mass), add 62.5g of 4.6% by mass nitric acid for dispersion, and then add 200g of deionized water to obtain aluminum hydroxide slurry with a solid content of 20% by mass.
[0120] (2) Preparation of aluminum hydroxide pellets
[0121] The aluminum hydroxide slurry prepared in step (1) is dripped into the oil-ammonia column. The upper layer of the oil-ammonia column is the oil phase, and the lower layer is the ammonia water phase. The upper oil phase is 4 cm thick n-octane, and the lower ammonia water phase is 160 cm thick ammonia water with a concentration of 8% by mass. The aluminum hydroxide slurry is dripped into the oil phase in the oil-ammonia column to form small balls, and then enters the ammonia water phase and stays in the ammonia water phase for 2 hours to solidify, forming wet aluminum hydroxide small balls, which are collected at the bottom of the oil-ammonia column. The wet aluminum hydroxide small balls are taken out and pre-dried: first, the temperature is increased to 50°C at a heating rate of 2°C / min, and dried for 30 minutes, and then the temperature is increased to 100°C at a heating rate of 8°C / min, and dried for 90 minutes.
[0122] (3) Preparation of alumina balls
[0123] The pre-dried aluminum hydroxide balls were collected for aging. The specific steps were as follows: the pre-dried aluminum hydroxide balls were placed in 300 mL of n-heptanol and aged at 100°C for 6 hours. After aging, the n-heptanol was filtered out to obtain aged aluminum hydroxide balls. The aged aluminum hydroxide balls were treated at 120°C for 10 minutes under the action of water vapor. The volume space velocity of the water vapor was 400 h / min. -1 The aluminum hydroxide balls treated with water vapor were dried at 80°C for 8 hours, 120°C for 4 hours, and then calcined at 600°C for 3 hours to obtain γ-Al2O3 small ball particles with smooth outer surface. The sphericity, crushing strength, bulk density and pore volume of the γ-Al2O3 small balls were measured, and the results are shown in Table 1.
[0124] Example 3
[0125] (1) Preparation of aluminum hydroxide slurry
[0126] Take 100g of pseudo-boehmite powder (alumina content of 72.5% by mass), add 62.5g of 4.6% by mass nitric acid for dispersion, and then add 200g of deionized water to obtain aluminum hydroxide slurry with an alumina solid content of 20% by mass.
[0127] (2) Preparation of aluminum hydroxide pellets
[0128] The aluminum hydroxide slurry prepared in step (1) is dripped into the oil-ammonia column. The upper layer of the oil-ammonia column is the oil phase, and the lower layer is the ammonia water phase. The upper oil phase is 5 cm thick n-octane, and the lower ammonia water phase is 150 cm thick ammonia water with a concentration of 8% by mass. The aluminum hydroxide slurry is dripped into the oil phase in the oil-ammonia column to form small balls, and then enters the ammonia water phase and stays in the ammonia water phase for 5 hours to solidify, forming wet aluminum hydroxide small balls, which are collected at the bottom of the oil-ammonia column. The wet aluminum hydroxide small balls are taken out and pre-dried: first, the temperature is increased to 48°C at a heating rate of 1°C / min, and dried for 90 minutes, and then the temperature is increased to 120°C at a heating rate of 6°C / min, and dried for 30 minutes.
[0129] (3) Preparation of alumina balls
[0130] The pre-dried aluminum hydroxide balls were collected for aging. The specific steps were as follows: the pre-dried aluminum hydroxide balls were placed in 300 mL of n-butanol and aged at 80°C for 18 hours. After aging, the n-butanol was filtered out to obtain aged aluminum hydroxide balls. The aged aluminum hydroxide balls were treated at 120°C for 20 minutes under the action of water vapor. The volume space velocity of the water vapor was 300 h / min. -1 The aluminum hydroxide balls treated with water vapor were dried at 80°C for 8 hours, 120°C for 4 hours, and then calcined at 600°C for 3 hours to obtain γ-Al2O3 small ball particles with smooth outer surface. The sphericity, crushing strength, bulk density and pore volume of the γ-Al2O3 small balls were measured, and the results are shown in Table 1.
[0131] Example 4
[0132] γ-Al2O3 pellets were prepared according to the method of Example 1, except that the pre-drying conditions of the wet aluminum hydroxide pellets in step (2) were: firstly heated to 40°C at a heating rate of 2°C / min, dried for 90 minutes, then heated to 100°C at a heating rate of 6°C / min, and dried for 150 minutes to obtain γ-Al2O3 pellet particles. The sphericity, crushing strength, bulk density and pore volume of the γ-Al2O3 pellets were measured, and the results are shown in Table 1.
[0133] Example 5
[0134] γ-Al2O3 pellets were prepared according to the method of Example 1, except that the pre-drying conditions of the wet aluminum hydroxide pellets in step (2) were: firstly heated to 50°C at a heating rate of 3°C / min, dried for 60 minutes, then heated to 80°C at a heating rate of 8°C / min, and dried for 180 minutes to obtain γ-Al2O3 pellet particles. The sphericity, crushing strength, bulk density and pore volume of the γ-Al2O3 pellets were measured, and the results are shown in Table 1.
[0135] Example 6
[0136] γ-Al2O3 pellets were prepared according to the method of Example 1, except that the steam treatment conditions in step (3) were: treatment at 110°C for 30 minutes, and the volume space velocity of the steam was 400 h -1 , and obtain γ-Al2O3 pellet particles. The parameters such as sphericity, crushing strength, bulk density and pore volume of γ-Al2O3 pellet D were measured, and the results are shown in Table 1.
[0137] Example 7
[0138] γ-Al2O3 pellets were prepared according to the method of Example 1, except that the steam treatment conditions in step (3) were: treatment at 150°C for 12 minutes, and the volume space velocity of the steam was 400 h -1 The sphericity, crushing strength, bulk density and pore volume of γ-Al2O3 pellet E were measured, and the results are shown in Table 1.
[0139] Example 8
[0140] The γ-Al2O3 pellets were prepared according to the method of Example 1, except that the steam treatment conditions in step (3) were: 200°C for 50 minutes, with a steam space velocity of 100 h -1 The sphericity, crushing strength, bulk density and pore volume of γ-Al2O3 pellet E were measured, and the results are shown in Table 1.
[0141] Example 9
[0142] γ-Al2O3 pellets were prepared according to the method of Example 1, except that the pre-drying conditions of the wet aluminum hydroxide pellets in step (2) were: first heated to 60°C at a heating rate of 5°C / min, dried for 20 minutes, then heated to 80°C at a heating rate of 10°C / min, and dried for 120 minutes. The sphericity, crushing strength, bulk density and pore volume of the γ-Al2O3 pellets were measured, and the results are shown in Table 1.
[0143] Comparative Example 1
[0144] γ-Al2O3 pellets were prepared according to the method of Example 1, except that the aluminum hydroxide wet balls collected at the bottom of the oil-ammonia column in step (2) were not pre-dried but directly aged to obtain γ-Al2O3 pellet particles. The parameters of the γ-Al2O3 pellets, such as sphericity, crushing strength, bulk density and pore volume, were measured. The results are shown in Table 1.
[0145] Comparative Example 2
[0146] γ-Al2O3 pellets were prepared according to the method of Example 1, except that the aluminum hydroxide pellets after aging treatment in step (3) were not subjected to steam treatment, but directly dried and calcined to obtain γ-Al2O3 pellet particles. The sphericity, crushing strength, bulk density and pore volume of the γ-Al2O3 pellets were measured, and the results are shown in Table 1.
[0147] Table 1
[0148]
[0149]
[0150] It can be seen from the results in Table 1 that the γ-Al2O3 spheres prepared by the preparation method of the present invention have significantly improved sphericity compared with the γ-Al2O3 spheres prepared in Comparative Examples 1-2. 0.95 The crushing strength is greatly improved, and the spherical alumina of the present invention is significantly increased, so that the catalysts for continuous reforming, low-carbon alkane dehydrogenation, etc., which use the spherical alumina as a carrier, are not easy to break during use, the attrition rate is reduced, and the service life of the catalyst is extended.
[0151] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing spherical alumina, the method comprising the following steps: (1) dropping aluminum hydroxide slurry into a spheroidizing column to form wet aluminum hydroxide spheres, and then pre-drying the wet aluminum hydroxide spheres; (2) aging the pre-dried product in the presence of a solvent; (3) The product obtained by aging in step (2) is subjected to steam treatment at 100-240° C., and then optionally dried and calcined.
2. The method according to claim 1, wherein: The pre-drying in step (1) includes a first pre-drying and a second pre-drying; Preferably, the first pre-drying conditions include: temperature of 30-60°C, preferably 30-50°C; time of 20-180 minutes, preferably 30-120 minutes; Preferably, the heating rate of the first pre-drying is 1-5°C / min, preferably 1-3°C / min; Preferably, the second pre-drying conditions include: temperature of 70-120°C, preferably 90-120°C; time of 30-420 minutes, preferably 30-180 minutes; Preferably, the heating rate of the second pre-drying is 5-10°C / min, preferably 5-8°C / min.
3. The method according to claim 1, wherein: The solid content of the aluminum hydroxide slurry is 6-25wt%; Preferably, the aluminum hydroxide slurry is obtained by mixing an aluminum-containing precursor, an acid and water; Preferably, the mass ratio of the acid to the aluminum-containing precursor is 0.01-0.06, wherein the aluminum-containing precursor is calculated as aluminum oxide; Preferably, the aluminum-containing precursor is pseudo-boehmite and / or boehmite; Preferably, the acid is an inorganic acid and / or an organic acid; Preferably, the inorganic acid is nitric acid and / or hydrochloric acid, and the organic acid is formic acid and / or acetic acid; Preferably, the acid is provided in the form of an acid solution, and the concentration of the acid solution is 0.5-6% by mass.
4. The method according to claim 1, wherein: The spheroidizing column comprises an organic phase and an ammonia aqueous phase, and the ratio of the thickness of the organic phase to the thickness of the ammonia aqueous phase is 1:10-80, preferably 1:20-60; Preferably, the organic phase is C5-C 20 Alkanes, preferably at least one selected from gasoline, kerosene, petroleum ether, n-pentane, n-hexane, n-heptane, n-octane and undecane; Preferably, the concentration of the aqueous ammonia is 5-15% by mass.
5. The method according to any one of claims 1 to 4, wherein: The step (1) of dripping the aluminum hydroxide slurry into the sphering column to form wet aluminum hydroxide pellets comprises: dripping the aluminum hydroxide slurry into the organic phase of the sphering column to form pellets, and then entering the ammonia water phase to solidify for 0.2-12 hours to form wet aluminum hydroxide pellets.
6. The method according to any one of claims 1 to 5, wherein: The aging conditions in step (2) include: a temperature of 60-300° C., preferably 60-220° C.; a time of 5-30 hours, preferably 5-20 hours; Preferably, the solvent is selected from C4-C 10 Fatty alcohols and / or C5-C 20 of alkanes; Preferably, the C4-C 10 The fatty alcohol is selected from at least one of n-butanol, n-pentanol, n-hexanol, n-heptanol and n-octanol; Preferably, the C5-C 20 The alkane is selected from at least one of pentane, hexane, heptane, octane, nonane, decane and petroleum ether.
7. The method according to any one of claims 1 to 6, wherein: The temperature of the water vapor treatment in step (3) is 100-180°C; Preferably, the steam treatment time in step (3) is 10-60 minutes, preferably 10-30 minutes; Preferably, the volume space velocity of the water vapor is 100-1000h -1 ; preferably 200-600h -1 .
8. The method according to any one of claims 1 to 7, wherein: The drying conditions in step (3) include: a temperature of 50-150° C. and a time of 5-24 hours; Preferably, the calcination temperature in step (3) is 450-750° C. and the calcination time is 2-10 hours.
9. Spherical alumina prepared by the method according to any one of claims 1 to 8; Preferably, the sphericity of the spherical alumina is greater than 0.99; Preferably, the Q of the spherical alumina is 0.95 Greater than 98% by volume, of which Q 0.95 is the volume proportion of spherical alumina particles with a sphericity greater than 0.95 in all spherical alumina particles; Preferably, the crushing strength of the spherical alumina is 80-130N / grain.
10. Use of the spherical alumina according to claim 9 in catalysts.
Citation Information
Patent Citations
Method for preparing spherical alumina
CN101850997A
Method for preparing spherical alumina by virtue of oil ammonia column
CN103011213A
Chambering method for spherical aluminum oxide particles
CN104891539A
Gamma alumina, preparation method and application thereof and device
CN106348326A
Preparation method of spherical aluminum oxide
CN113735614A
